The regenerative capacity of skeletal muscle in experienced endurance runners - Collins, M.; Rae, D. E.; Vignaud, A.; Linström, M.; Thornell, L. E.; Butler-Browne, G. S.; Sinclair-Smith, C.; Derman, E. W.; Lambert, M. I. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The muscle of distance runners has presumably sustained numerous cycles of exercise-associated damage and regeneration or remodelling. Whether this interferes with the finite regenerative capacity of the skeletal muscle in asymptomatic runners is not known. To assess the chronic effects of a large exposure to running on muscle, this study compared markers of remaining regenerative capacity in the muscle of experienced endurance runners to that of sedentary controls. Methods: Biopsies of the vastus lateralis muscle from 19 experienced endurance runners (ATH) (mean age: 43±7 years) were compared to those of 19 sedentary individuals (SED) (mean age: 39±10 years). The runners had covered approximately 50 000 km in training and racing over 15 years. Laboratory analysis determined the proportion of satellite cells present, terminal restriction fragment (TRF) lengths and morphology of the muscle samples. Results: The proportion of satellite cells (number of satellite cells per number of myonuclei) present in the muscle of the runners was similar to that of the controls (ATH 3.8 ± 1.5 % vs CON 3.0 ± 0.7 %, p=0.377). There were also no differences in the minimum TRF lengths (ATH 6.9 ± 0.9 kbp vs CON 7.0 ± 0.8 kpb, p=0.805), in the muscle of both groups. The minimum TRF length of the runners was, however, inversely related to their years in distance running (r= -0.63, p=0.007) and hours spent training (r=-0.51, p=0.034). Conclusion: The remaining regenerative capacity of the muscle of experienced runners was no more compromised than that of sedentary individuals despite the increased demand for skeletal muscle repair, regeneration and adaptation. Skeletal muscle appears to be a robust organ with sufficient capacity to tolerate large exposures to endurance running.